Morphotypology Of High-level Weightlifters : Anthropometry And Somatotypy. - Ali , Touami; Nabila, Mimouni; Touami , Mohamed Amine (Journal of Sport Science Technology and Physical Activities, 2025)
Weightlifting is a discipline where technique and anthropometric characteristics are essential to achieve the best results in competition. This study aims to describe the morphological characteristics of high-level Arab and African weightlifters. We measured anthropometric parameters, calculated physical development indices and determined somatotype using the Heath-Carter method. The aim of this method is to analyze the relationships between body composition and somatotype in high-level weightlifters. To do this, we used anthropometric methods based on the methodology of the International Society for the Advancement of Kinanthropometry (ISAK), calculated body composition according to Mateigka and physical development indices specific to weightlifters. Forty-four high-level weightlifters were evaluated using anthropometric methods. We calculated body composition and determined somatotypes. The results reveal a mesomorphic dominance associated with a high muscle mass, adapted to the explosive strength requirement of the discipline.